Neutrophil extracellular traps and their implications in airway inflammatory diseases - Xuan, Nanxia; Zhao, Jie; Kang, Zhiying; Cui, Wei; Tian, Bao-ping (Frontiers in Medicine, 2024)
Neutrophil Extracellular Traps (NETs) are essential for immune defense and have been increasingly recognized for their role in infection and inClammation.In the context of airway inClammatory diseases, there is growing evidence suggesting the involvement and signiCicance of NETs. This review aims to provide an overview of the formation mechanisms and components of NETs and their impact on various airway inClammatory diseases, including acute lung injury/ARDS, asthma, chronic obstructive pulmonary disease (COPD) and cystic Cibrosis. By understanding the role of NETs in airway inClammation, we can gain valuable insights into the underlying pathogenesis of these diseases and identify potential targets for future therapeutic strategies that either target NETs formation or modulate their harmful effects. Further research is warranted to elucidate the complex interactions between NETs and airway inClammation and to develop targeted therapies that can effectively mitigate their detrimental effects while preserving their beneCicial functions in host defense.